ENVIRONMENTAL AWARENESS PERCEPTION OF YOUNG PEOPLE LIVING IN THE BIOSPHERE RESERVE IN LATVIA - Druva-Druvaskalne, Iveta; Livina, Agita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Environmental education issues are topical at all levels of education, from kindergarten to lifelong learning. The focus of this study was on young people. Vidzeme University of Applied Sciences (ViA) is located in Vidzeme region in Latvia, where the only biosphere reserve in Latvia is located. ViA researchers started research in this area already in 2006, surveying the local population on environmental, social and economic issues in 2007. In 2018 ViA students repeatedly carried out a study of this area by surveying young people up to the age of 19 (n = 120) with an aim of exploring the views of young people living in the biosphere reserve on environmental issues. Environmental awareness is one of the key factors influencing people's behaviour in deciding on a sustainable lifestyle.The European Union regularly conducts research of its citizens on environmental issues. In the latest report the respondents from Latvia have shown one of the lowest indicators when responding to the statement "You can participate in environmental protection yourself" – 76% agree with this statement, in comparison with, for example, the Netherlands – 97%, Sweden – 96%. The youth survey in a face-to-face form was conducted from April to May 2018; it was done by the students and the obtained results were analyzed and compared with the study of 2007 by the authors of the article to characterize the trends in the perception of young people of environmental issues in a specially protected nature territory.The perception of environmental issues was analyzed according to Bolscho environmental awareness dimensions. In general, the understanding and knowledge of environmental issues of the young people surveyed living in the territory of North Vidzeme Biosphere Reserve (NVBR) is positive, especially on resource-responsible, economical use. In terms of attitudes and values, young people express their support for the preservation of cultural traditions. With regard to the visibility of the NVBR, more work is required to explain the functions and possibilities of the NVBR. Compared to 2007, the feeling of pride of the fact that a respondent lives in a protected nature area has increased.